Chronic thromboembolic pulmonary hypertension following pulmonary embolism with a right ventricular thrombus: A report of two cases. (1st May 2021) - Zhang, Tailong; Liang, Weitao; Bian, Longrong; Wu, Zhong
Abstract : Right heart thrombus accompanied by chronic thromboembolic pulmonary hypertension is a rare entity. Right heart thrombus may develop in the peripheral veins or in situ within the right heart chambers. The diagnosis of right heart thrombus is challenging, since its symptoms are typically non‐specific and its imaging features resemble those of cardiac masses. Here, we report two cases of right heart thrombus with chronic thromboembolic pulmonary hypertension that presented as right ventricular masses initially. Both patients underwent simultaneous pulmonary endarterectomy and resection of the ventricular thrombi. Thus, when mass‐like features are confirmed by imaging, right heart thrombus should be suspected in patients with chronic thromboembolic pulmonary hypertension, and simultaneous right heart thrombus resection is required along with pulmonary endarterectomy.